A conductor's standpoint: an institutional ethnography of a conductive education centre in Birmingham, UK. (6th November 2020) - Blackburn, Carolyn; Ward, Karen
ABSTRACT: Conductive Education (CE) is a means of 'bringing together' and involves a unified, integrated approach to educating children with disabilities to maximise the effects of teaching and learning. Conductive pedagogues ('conductors') are educators trained and socialised to work according to this holistic philosophy. First developed in Hungary by Andras Peto CE is now an internationally recognised pedagogical approach with 200 CE centres in 24 countries across the world. Despite the focus on education, the majority of published research on CE compares CE to health based rehabilitation or intervention approaches where learners are referred to as patients creating issues of identity for Conductors. By contrast this study is the first to explore the professional working practices in the children's services provision of a CE Centre in Birmingham, UK drawing on Institutional Ethnography (IE) as a novel way to think otherwise about methodology and research creatively across disciplines. In a small scale study using interviews, observations and document analysis, the findings highlight the 'relations of ruling' that shape local experiences. The empirical linkages in the everyday life, organisation and translocal processes of administration and Governance within the centre have emerged and revealed the complex field of co-ordination and control arising from special educational needs and disabilities regulatory practice that influence Conductors' working lives. The findings of the study suggest that Conductors work creatively with other disciplines to foreground children's strengths and competencies, challenging orthodoxies of (dis)ability and deficit and position their own professional practice in education as complimentary and family-centred. The study adds a unique insight to the professional lives of Conductors.